Clinical characteristics and etiological profile of retropharyngeal space abnormalities in children: a nine-year retrospective analysis - Hao, Lili; Wei, Youhua; Lin, Jiahui; Li, Juan; Xia, Zhongfang (Frontiers in Pediatrics, 2026)
ObjectiveTo analyze the clinical characteristics and etiological spectrum of retropharyngeal space abnormalities in children, stratifying by age to improve diagnostic and therapeutic strategies.MethodsWe retrospectively analyzed the clinical data of 77 pediatric patients with imaging-confirmed retropharyngeal space abnormalities admitted to Wuhan Children's Hospital between January 2015 and March 2024. Patients were divided into two groups based on age: younger group (<6 years, n = 51) and older group (≥6 years, n = 26). Demographics, clinical presentations, imaging findings, etiologies, and treatment outcomes were compared between the groups using Chi-square or Fisher's exact tests for categorical data and independent samples t-tests for continuous data.ResultsThe most common presenting symptoms were fever (49.4%) and neck mass (33.8%). The primary CT finding was retropharyngeal hypodensity or fluid collection (68.8%). No significant differences were observed in sex ratio, clinical symptoms, or imaging findings between the two age groups (p > 0.05). However, children <6 years old had a significantly higher rate of requiring transoral incision and drainage for retropharyngeal abscess (23.5% vs. 3.8%, p = 0.041). Etiologically, infectious diseases were significantly more prevalent in the older group (92.3% vs. 70.6%, p = 0.030), whereas congenital malformations were a more common underlying cause in the younger group, however, this trend did not reach statistical significance (p = 0.051).ConclusionThe etiology and management of pediatric retropharyngeal abnormalities are age-dependent; infectious causes dominate in children ≥6 years, while congenital malformations are key considerations in those <6 years, who are at higher risk for abscess formation requiring surgical intervention.